Analysis on aspects of traditional ('indigenous') and western-based thinking in the classical and modern burmese elites' discourse concerning madness - Myint, Zan (Universiti Kebangsaan Malaysia, 2010)
Excerpts from a translated Burmese text on what it termed the 'madness disease'is provide and commented on. It is asserted that the text confuses between causes, symptoms, etiology and treatment of the diseases but a classification can be made that the traditional text postulates that the causes of what it called the 'madness disease'can be divided into (a) physiological (b) psychological and (c)'esoteric'components. The text gives the most emphasis on madness being an 'affliction'which was caused when the subject is 'seized'or ...